Impact of the COVID-19 Pandemic on the Practice of Hand and Upper Extremity Surgeons - Qazi, Uzair A (Cureus, 2020)
Objective The purpose of this study was to determine the impact of the coronavirus disease 2019 (COVID-19) pandemic on the practice of hand and upper extremity surgeons. Methods We assessed how the pandemic affected the practice on multiple fronts including professional, personal, and practice aspects. The survey was conducted through an online questionnaire that had six sections: demographics, clinic, elective surgery, emergency surgery, urgent surgery, and human resources. The survey was sent to 586 Kleinert Society members who are all practicing hand and upper extremity surgeons. Results We received 35 responses from the United States and 53 from the rest of the world. Based on our findings, the clinic volume was reduced by >50% in the early stages, subsequently returning to a level that was 25-50% lower than pre-COVID-19 times in later stages. A corresponding decrease in elective surgeries was also noted. The need for preoperative COVID-19 tests added to the logistics of surgery, causing delays of three to six hours for emergency cases and >24 hours for urgent cases. The hand surgeons witnessed multiple furloughs, layoffs, and even COVID-19 infections among nursing and support staff. Most hand surgeons continued to perform urgent and emergency surgeries during the pandemic. The application of telemedicine was not popular and had multiple drawbacks. Hand surgeons are modifying their practice by adopting measures such as social distancing, reducing the clinic volume, and using personal protective equipment (PPE). Conclusions As COVID-19 is likely to prevail for the foreseeable future, these measures are here to stay. The initial reduction in the clinic and elective volume has improved but has not reached pre-COVID-19 levels, suggesting a slow recovery. As reopening measures will lead to more people rejoining employment, subsequently, more patients with hand-related conditions are likely to present to the clinics. Rapid COVID-19 testing and supply of PPEs will play a crucial role in the near future to enable hand surgeons to continue their service while taking care of their personal health.